(untitled) (Colombia Medica, 2018)
A Savior Sibling is a child who is born to provide an organ, bone marrow or cell transplant, to a sibling that is affected with a fatal disease. There are created with the in vitro fertilization and pre-implantation genetic diagnosis and, in the process, the ethical standards for organ donation of children become less demanding. Therefore, we propose that the authorization of the technique considers, unavoidably, the opinion of an impartial third party that can guarantee the welfare of the child. We develop a critical analysis of the laws that regulate the creation of babies to serve as organ donors. We evaluate under what circumstances the organizations that play a part in the decisions, fulfill the ethical standards to allow the organ donation of children.